A Novel Lumbar Motion Segment Classification to Predict Changes in Segmental Sagittal Alignment After Lateral Interbody Fixation. (October 2017) - Acosta, Frank L.; Mehta, Vivek A.; Arakelyan, Anush; Drazin, Doniel; Cortland, Clarissa; Hsieh, Patrick C.; Liu, John C.; Pham, Martin H.
Study Design: Retrospective cohort study. Objectives: Lateral interbody fixation is being increasingly used for the correction of segmental sagittal parameters. One factor that affects postoperative correction is the resistance afforded by posterior hypertrophic facet joints in the degenerative lumbar spine. In this article, we describe a novel preoperative motion segment classification system to predict postoperative correction of segmental sagittal alignment after lateral lumbar interbody fusion. Methods: Preoperative computed tomography scans were analyzed for segmental facet osseous anatomy for all patients undergoing lateral lumbar interbody fusion at 3 institutions. Each facet was assigned a facet grade (min = 0, max = 2), and the sum of the bilateral facet grades was the final motion segment grade (MSG; min = 0, max = 4). Preoperative and postoperative segmental lordosis was measured on standing lateral radiographs. Postoperative segmental lordosis was also conveyed as a percentage of the implanted graft lordosis (%GL). Simple linear regression was conducted to predict the postoperative segmental %GL according to MSG. Results: A total of 36 patients with 59 operated levels were identified. There were 19 levels with MSG 0, 14 levels with MSG 1, 13 levels with MSG 2, 8 levels with MSG 3, and 5 levels with MSG 4. Mean %GL was 115%, 90%, 77%, 43%, and 5% for MSG 0 to 4, respectively. MSG significantly predicted postoperative %GL ( P < .01). Each increase in MSG was associated with a 28% decrease in %GL. Conclusions: We propose a novel facet-based motion segment classification system that significantly predicted postoperative segmental lordosis after lateral lumbar interbody fusion.